An exploratory study of predictors of vocabulary knowledge of Vietnames preschool-age children in a city: Predictors of vocabulary knowledge in Vietnamese preschoolers - Hoang, Giang Thi Huong; Baten, Kristof; de Cuypere, Ludovic; Hoang, Tat Thang; Taverniers, Miriam (Dutch Journal of Applied Linguistics, 2021)
This study explores the effects of child-external and child-internal factors on vocabulary skills of Vietnamese pre-schoolers. Thirty-nine Vietnamese children (54-77 months) were tested on vocabulary and cognition skills. Their parents completed a questionnaire on background information. Correlation and regression analyses were performed to explore the contribution of multiple factors to the variability in vocabulary skills. Results showed that the effects of multiple factors varied across modality and domain. Productive vocabulary was individually sensitive to more factors than receptive vocabulary; and phonologically-based vocabulary was more sensitive than semantically-based vocabulary. The strongest predictor of receptive vocabulary, productive vocabulary, semantically-based vocabulary and phonologically-based vocabulary was child intelligence, child pre-schooling length, household income and child age, respectively. The findings seem to support the multidimensional views of language with evidence that different domains or modalities of vocabulary skills respond to the effects of multiple factors differently; and components of verbal ability should be examined separately.